2012
DOI: 10.1208/s12249-012-9805-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Formulation Variables and Excipient Interaction on the Production of Niosomes

Abstract: Abstract. The aim of this study was to investigate the effects of formulation and process variables on the properties of niosomes formed from Span 40 as nonionic surfactant. A variety of formulations encapsulating Paclitaxel, a hydrophobic model drug, were prepared using different dicetyl phosphate (DCP) and Span 40-cholesterol (1:1) amounts. Formulations were optimized by multiple regression analysis to evaluate the changes on niosome characteristics such as entrapment efficiency, particle size, polydispersit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 25 publications
5
41
0
Order By: Relevance
“…The selected Span 1 60/CH/DCP niosomal dispersion was then subjected to sonication, for different times and power intensity, in order to find the best conditions to suitably further reduce the vesicle dimensions (Sezgin-Bayindir and Yuksel, 2012). The results, summarized in Table 3, showed that 2 h sonication at 100 W caused an about 3 times reduction of vesicle particle size, without affecting the drug entrapment efficiency.…”
Section: Niosomes Preparation and Characterizationmentioning
confidence: 99%
“…The selected Span 1 60/CH/DCP niosomal dispersion was then subjected to sonication, for different times and power intensity, in order to find the best conditions to suitably further reduce the vesicle dimensions (Sezgin-Bayindir and Yuksel, 2012). The results, summarized in Table 3, showed that 2 h sonication at 100 W caused an about 3 times reduction of vesicle particle size, without affecting the drug entrapment efficiency.…”
Section: Niosomes Preparation and Characterizationmentioning
confidence: 99%
“…(2014) [1][2][3][4][5][6][7][8][9][10][11][12][13] www.deswater.com doi: 10.1080/19443994.2014.993726 attractiveness of these vesicles for industrial production [10,11]. Encapsulation efficiency depends on several factors such as the type of structure (multilamellar, unilamellar, or multivesicular), the length of the hydrophobic group of surfactant forming the bilayer, the nature and size of the hydrophilic head, pH and composition of the formulation medium, and the nature of the solute (hydrophobicity, polarity, molecular weight, and structure).…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Moreover, their large-scale production without using unacceptable solvents is uncomplicated, so they are widely used in pharmaceutical, cosmetic and, to a lesser extent, food applications [19][20][21][22][23]. Another advantage for industrial production of these vesicles is the large number of non-toxic and relatively low-cost non-ionic surfactants available for niosome formulation [24]. Encapsulation efficiency depends mainly on niosome structure, the nature and size of the hydrophilic head and the length of the hydrophobic group of surfactant forming the bilayer, pH and composition of the formulation medium, and the nature of the solute [25][26][27].…”
Section: Introductionmentioning
confidence: 99%